2012
DOI: 10.1017/s1751731111002643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding programme on the performance and energy balance of nulliparous rabbit does

Abstract: A total of 190 rabbit females were used to evaluate five feeding programmes from 9 weeks of age to the first parturition: CAL, fed ad libitum with a control diet (C: 11.0 MJ digestible energy (DE) and 114 g digestible protein (DP)/kg dry matter (DM)) until first parturition; CR, fed ad libitum with C diet until 12 weeks of age and then C diet restricted (140 g/day) until first parturition; F, fed ad libitum with a low-energy, high-fibre diet (F: 8.7 MJ DE and 88 g DP/kg DM) until first parturition; FC, fed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 34 publications
5
45
0
Order By: Relevance
“…The data on body weight, feed intake, blood metabolites and hormones were similar to those obtained by other authors (Rommers et al, 2004;Brecchia et al, 2006;García-García et al, 2011;Rebollar et al, 2011;Menchetti et al, 2015a;Martínez-Paredes et al, 2012), except for blood glucose and insulin concentrations at 20 th wk of age, which were very low in all groups. Compared with values at 13 th wk of age, blood glucose fell in mid gestation, as a result of its increased metabolic demand by foetal and maternal tissues (Fortum-Lamothe, 2006) and, accordingly, circulating insulin concentration also decreased.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The data on body weight, feed intake, blood metabolites and hormones were similar to those obtained by other authors (Rommers et al, 2004;Brecchia et al, 2006;García-García et al, 2011;Rebollar et al, 2011;Menchetti et al, 2015a;Martínez-Paredes et al, 2012), except for blood glucose and insulin concentrations at 20 th wk of age, which were very low in all groups. Compared with values at 13 th wk of age, blood glucose fell in mid gestation, as a result of its increased metabolic demand by foetal and maternal tissues (Fortum-Lamothe, 2006) and, accordingly, circulating insulin concentration also decreased.…”
Section: Discussionsupporting
confidence: 87%
“…However, T3 concentration was higher at 13 th wk, as required in a growing animal due to the function of T3 in animal growth. Martínez-Paredes et al (2012) found an increase in T3 values from 9 to 18 wk of age.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…There is also a considerable fatty deposition in the liver so intense that it may interfere with the liver function (Bruss, 1997). Episodes of pregnancy toxaemia can be surmised in rabbit does, which lead females to higher mobilization of reserves in late pregnancy (Rommers et al, 2004;Martínez-Paredes et al, 2012). Subsequently, body reserves are recovered during the first stage of lactation and reach a maximum around day 10 in lactation (Quevedo et al, 2007).…”
Section: Effect Of Transition Period In Reproductive Rabbit Doesmentioning
confidence: 99%